2016
DOI: 10.18845/tm.v29i8.2982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación técnica de dos métodos de compostaje para el tratamiento de residuos sólidos biodegradables domiciliarios y su uso en huertas caseras

Abstract: <p class="p1">La necesidad de plantear soluciones para apoyar la gestión integral de los residuos sólidos biodegradables ha llevado a proponer métodos de tratamiento como el compostaje, el cual consiste en la transformación de residuos sólidos por medios biológicos, bajo condiciones controladas, en productos como abono, sustrato o enmiendas  para la agricultura. Por esto, se evaluó técnicamente dos métodos de compostaje de residuos sólidos biodegradables con miras a utilizar el abono resultante en huerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
2
6
0
9
Order By: Relevance
“…Accordingly, with the humidity results presented, the absence of leachate in the composting process would be expected. This was confirmed in this study when a TCB or composter barrel was used, and confirmed by other authors [16][17][18]20]. This is explained owing to the high temperatures developed during the composting process (54-60 • C, Table 2) and because the composting was conducted in open systems, which reduced the excess humidity.…”
Section: Humidity and Phsupporting
confidence: 89%
See 4 more Smart Citations
“…Accordingly, with the humidity results presented, the absence of leachate in the composting process would be expected. This was confirmed in this study when a TCB or composter barrel was used, and confirmed by other authors [16][17][18]20]. This is explained owing to the high temperatures developed during the composting process (54-60 • C, Table 2) and because the composting was conducted in open systems, which reduced the excess humidity.…”
Section: Humidity and Phsupporting
confidence: 89%
“…However, these TCBs were fed by household food waste and processed in a backyard. Considering the latter results in comparison to those reported here for the Chemistry Department, for example, a TCB for 31 persons processed 0.59 kg day −1 , it could be expected that a TCB located in a workplace could perform well for around 80 people if one TCB could receive 1.5 kg day −1 , as reported by Campos-Rodríguez et al [18].…”
Section: Tcb Operation: Feeding and Quantificationsupporting
confidence: 83%
See 3 more Smart Citations